2020
DOI: 10.1007/s12020-020-02508-w
|View full text |Cite
|
Sign up to set email alerts
|

Combined molecular and mathematical analysis of long noncoding RNAs expression in fine needle aspiration biopsies as novel tool for early diagnosis of thyroid cancer

Abstract: Purpose In presence of indeterminate lesions by fine needle aspiration (FNA), thyroid cancer cannot always be easily diagnosed by conventional cytology. As a consequence, unnecessary removal of thyroid gland is performed in patients without cancer based on the lack of optimized diagnostic criteria. Aim of this study is identifying a molecular profile based on long noncoding RNAs (lncRNAs) expression capable to discriminate between benign and malignant nodules. Methods Patients were subjected to surgery (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…The performance of a smaller mutation panel combined with an miRNA risk classifier (ThyGeNEXT + ThyraMIR) was recently validated in a multicenter study [89], which reported good sensitivity (95%) and specificity (90%) for malignancy in indeterminate nodules. Some other, potentially less expensive, molecular tests were recently proposed, but need prospective and multicenter validation; these include a dual-component molecular assay (an extended DNA and RNA mutation panel plus a single miRNA expression level) [90], and the analysis of selected long non-coding RNAs (MALAT1, HOTAIR, PVT1) [91].…”
Section: Molecular Diagnosticsmentioning
confidence: 99%
“…The performance of a smaller mutation panel combined with an miRNA risk classifier (ThyGeNEXT + ThyraMIR) was recently validated in a multicenter study [89], which reported good sensitivity (95%) and specificity (90%) for malignancy in indeterminate nodules. Some other, potentially less expensive, molecular tests were recently proposed, but need prospective and multicenter validation; these include a dual-component molecular assay (an extended DNA and RNA mutation panel plus a single miRNA expression level) [90], and the analysis of selected long non-coding RNAs (MALAT1, HOTAIR, PVT1) [91].…”
Section: Molecular Diagnosticsmentioning
confidence: 99%
“…We first sought to profile the expression of H1R and H2R in MSNs of the NAc by using a single cell approach. For this, we assessed H2R and H1R mRNA levels in MSNs using a protocol that combines whole‐cell patch‐clamp recordings with high‐quality single cell RNA analysis by ddPCR (single‐cell qRT‐ddPCR) (Cadwell et al., 2016; Possieri et al., 2021). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…RNA was extracted from mouse NAc and cortex (Ctx) tissues using Trizol after tissue homogenization (homogenizer VDI12, VWR). RNA extraction, cDNA preparation and real-time PCR with Syber Green on QuantStudio 5 System (Applied Biosystems, Foster City, CA, USA) was performed as in Possieri et al (2021). Primers are as follows: HRH1 F 5 -CATCACTCCCTAGGACAGCC-3 , R 5 -GTCCTGTT CCCCTCACACAT-3 ; HRH2 F 5 -AGCTCCTATGACC CCAGAAAGAGT-3 , R 5 -TGGTGCCTGTTTCCATCG A-3 ; KCND2 F 5 -GGCAGCCTTCTGGTACACCAT-3 ; R 5 -GCACGGGTAGCGCAATG-3 ; GAPDH F 5 -TGC ACCACCACCTGCTTAGC-3 , R 5 -GTCTTCTGGGTG GCAGTGATG-3 .…”
Section: Rna Extraction and Rt-pcrmentioning
confidence: 99%
“…Besides their involvement in genomic imprinting, inactivation of chromosome X, maintenance of pluripotency, and the formation of different organs via changes in chromatin, transcription, and translation, they are also known to act as tumor suppressor genes or oncogenes. Recently, Possieri et al (37) analyzed six cancer-associated lncRNAs (MALAT1, NEAT1, HOTAIR, H19, PVT1, MEG3) in 135 FNA samples, with MALAT1, PVT1, and HOTAIR showing a significant differentiation capability between malignant and benign nodules (P < 0.0001).…”
Section: Contribution Of Epigenetic To Cytology Diagnostic Challengesmentioning
confidence: 99%